Seismic Response Study of Tunnels Running underneath a Subway Station in Parallel. (27th July 2020) - Sun, Fuxue; Wang, Guo-bo; Peng, Xiang-jun; Jin, Zhou-zhou; Li, Xiao-chun; Zhao, Jie-lin
Abstract : A tunnel passing below a metro station is taken as the object of our study, and a two-dimensional plane model is established to study the effects of their dynamic interaction to seismic excitation. Comparative analysis is used to obtain the influence law between the underground structures and on the soil. The results show that (1) the influence of the underground structure on the soil response is related to structure depth. The range of influence of the station structure on the surface is approximately five times the width of the station, and the surface response is obviously significant within this range. (2) The existence of the tunnel is conducive to reducing the acceleration of the column in the station. It increases the displacement difference between the stations, but the impact on the internal force of the station is not significant. (3) The influence of the station on the dynamic response of the tunnel is consistent with regard to tunnel acceleration, difference in displacement between the top and bottom of the tunnel, and internal force. The presence of the station will reduce the dynamic response of the tunnel.